2023
DOI: 10.1002/jad.12196
|View full text |Cite
|
Sign up to set email alerts
|

Family economic pressure and early adolescents' prosocial behavior: The importance of considering the types of prosocial behavior

Abstract: Background Prior research findings are mixed regarding whether prosocial behavior is positively or negatively related to socioeconomic status and its correlates, such as economic pressure. This may be due to the lack of considerations for the type of prosocial behavior. Aims In this study, we aimed to examine how six types of prosocial behavior (i.e., public, anonymous, compliant, emotional, dire, and altruistic) are related to economic pressure among early adolescents. We hypothesized that family economic pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…One suggested mechanism is that economic strain decreases capacity for empathy as an adaptive response to scarcity, which leads to decreased prosocial behavior (Jiang et al, 2020). Another study, grounded in the Family Stress Model, illustrates how family economic stress can negatively impact youth prosocial behavior (Xiao et al, 2023). Specifically, in a cross-sectional study with youth ages 11-14, Xiao et al (2023) found that economic pressure, also referred to as financial stress or strain, was negatively associated with two types of prosocial behavior (dire and emotional types).…”
Section: Financial Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…One suggested mechanism is that economic strain decreases capacity for empathy as an adaptive response to scarcity, which leads to decreased prosocial behavior (Jiang et al, 2020). Another study, grounded in the Family Stress Model, illustrates how family economic stress can negatively impact youth prosocial behavior (Xiao et al, 2023). Specifically, in a cross-sectional study with youth ages 11-14, Xiao et al (2023) found that economic pressure, also referred to as financial stress or strain, was negatively associated with two types of prosocial behavior (dire and emotional types).…”
Section: Financial Securitymentioning
confidence: 99%
“…Another study, grounded in the Family Stress Model, illustrates how family economic stress can negatively impact youth prosocial behavior (Xiao et al, 2023). Specifically, in a cross-sectional study with youth ages 11-14, Xiao et al (2023) found that economic pressure, also referred to as financial stress or strain, was negatively associated with two types of prosocial behavior (dire and emotional types). We apply this logic to examine financial security by hypothesizing that individuals in families with greater financial security are better positioned to give more social and emotional support to those around them given their lower strain and competition for resources.…”
Section: Financial Securitymentioning
confidence: 99%
“…Public prosocial behaviors are performed in the presence of others, which can create social pressure and the need to maintain a positive image [9]. In contrast, digital prosocial behaviors can be performed anonymously or with reduced social pressure, allowing individuals to engage in prosocial acts without the fear of judgment or scrutiny [13,14]. Another difference lies in the nature of the interactions.…”
Section: Introductionmentioning
confidence: 99%